Terapi Aromayoga untuk Menurunkan Berat Badan pada Akseptor KB Suntik - Ferina Ismaya; Lucky Herawati; Lanny Sunarjo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of yoga movements combined with aromatherapy (aromayoga) to reduce the weight of injectable birth control acceptors. The method used was true experimental with a pre-post test with a control design approach on 36 injectable birth control acceptors who experienced weight gain after injectable contraception, carried out 14 times in 2 months with a duration of 30 minutes. The analytical test was carried out using the Independent t-test analysis. The results showed a difference in the average weight loss in the intervention and control groups of 8.29 (p-value = 0.035) after two months of intervention. In conclusion, Aromayoga therapy affects losing weight, a side effect of injectable birth control. Keywords: Weight, Injectable Birth Control, Aromayoga Therapy